Editorial: Immune evasion strategies in Protozoan-Host interactions - Morrot, Alexandre (2020)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Imunoparasitologia. Rio de Janeiro, RJ, Brasil.